Placental Growth Factor in Assessment of Women With Suspected Pre-eclampsia to Reduce Maternal Morbidity: A Stepped Wedge Cluster Randomized Control Trial (PARROT Ireland). Issue 2 (February 2022) - Hayes-Ryan, D.; Khashan, A. S.; Hemming, K.; Easter, C.; Devane, D.; Murphy, D. J.; Hunter, A.; Cotter, A.; McAuliffe, F. M.; Morrison, J. J.; Breathnach, F. M.; Dempsey, E.; et al.
Abstract : (Abstracted from BMJ 2021;374:n1857) Placental growth factor (PlGF) has been suggested as a diagnostic biomarker of preeclampsia or placental dysfunction. PIGF typically circulates in maternal plasma and increases as placenta develops.